ChemInform Abstract: 1, n‐Hydrogen‐Atom Transfer (HAT) Reactions in Which n ≠ 5: An Updated Inventory. Issue 9 (March 2015) - Nechab, Malek; Mondal, Shovan; Bertrand, Michele P.
Abstract Review: [131 refs.